A Unique LnIII[3.3.1]GaIII Metallacryptate Series That Possesses Properties of Slow Magnetic Relaxation and Visible/Near‐Infrared Luminescence. Issue 42 (27th June 2018) - Lutter, Jacob C.; Eliseeva, Svetlana V.; Kampf, Jeff W.; Petoud, Stéphane; Pecoraro, Vincent L.
Abstract: A new family of [3.3.1] metallacryptates with the general composition [LnGa6 (H2 shi)(Hshi)(shi)7 (C5 H5 N)] (Ln‐1 ; shi 3− =salicylhydroximate; Ln = Pr, Nd, Sm–Yb) has been synthesized and characterized.Ln‐1 display both interesting magnetic and luminescent properties.Sm‐1 has sharp emission bands in the visible and the near‐infrared (NIR) regions with quantum yield values ( Q Sm L ) of 1.64(9) and 5.5(2) . 10 −2 %, respectively.Tb‐1 exhibits a weak green emission ( Q Tb L =1.89(3) . 10 −1 %) whilePr‐1, Nd‐1, Ho‐1, Er‐1, andYb‐1 possess emission bands in the NIR range with Q Pr L =3.7(2) . 10 −3 %, Q Nd L =1.71(5) . 10 −1 %, Q Ho L =1.1(2) . 10 −3 %, Q Er L =7.1(2) . 10 −3 % and Q Yb L =0.65(3) %.Nd‐1, Dy‐1, andYb‐1 display slow magnetization relaxation in an applied field, where onlyDy‐1 has been observed to follow an Orbach process ( U eff =12.7 K). The combination of NIR emission with magnetic properties makesNd‐1 andYb‐1 attractive candidates as smart materials addressable in two manners. Abstract : A two‐for‐one scaffold : A new Ln III ‐encapsulating metallamacrocyclic scaffold was synthesized and structurally determined to resemble cryptands. This metallacryptand can bind a wide variety of Ln III ions of different natures and demonstrates the ability to sensitize their characteristic emissions in the visible and/or near‐infrared. Slow magnetic relaxation was also observed for selected Ln III .